Pengembangan model pembelajaran matematika berbasis budaya melalui permainan tradisional jawa - Riani Ika Oktafianti; Riawan Yudi Purwoko; Erni Puji Astuti (Jurnal Inovasi Pendidikan Matematika (JIPM), 2019)
The purpose of this study was to develop a culture-based mathematics learning model through traditional Javanese games and find out the feasibility so that it could be used for elementary school students. This development research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Through these stages of development, it produce culture-based mathematics learning model through traditional Javanese games products with the main products in the form of model books, student books, teacher books, syllabus, lesson plans, and student worksheets. The research subjects were 19 fourth grade students at Klegenwonosari Elementary School. The data collection techniques in this study were carried out test and non-test. The data analysis technique in this study was in scores and percentages. Starting from the needs analysis of learning models, culture-based needs analysis, and curriculum analysis it is known that the use of mathematical learning models through traditional games has been done but outside learning, students were lack of knowledge about the traditional Javanese culture games that were Gobag Sodor and Engklek. Based on the results of the study, the mathematical learning model through traditional Javanese games fulfills the valid criteria with an average score of 3.79 from the model expert's assessment. Fulfill the effective criteria by obtaining the results of completeness of students 84.21% and get very positive students responses with a percentage of 90.90%. Therefore, Culture-based Mathmatics learning model through traditional Javanese games is suitable for elementary students.